Assessing George W. Bush's Legacy
X, 229 p.
Keywords: This book examines the legacy of the Bush presidency in term of presidential leadership, politics, and public policy. It focuses on Bush's expansion of presidential power in pursuit of the 'war on terror,' the ideological and pragmatic foundations of presidential politics, and the complexity of Bush's domestic and foreign policy legacies.